Converting between the oxides of nitrogen using metal–ligand coordination complexes. (7th October 2015) - Timmons, Andrew J.; Symes, Mark D.
<x xml:space="preserve">Abstract</x> The oxides of nitrogen (chiefly NO, NO3−, NO2− and N2O) are key components of the natural nitrogen cycle and are intermediates in a range of processes of enormous biological, environmental and industrial importance. In this Tutorial Review, we will examine catalysts for the inter-conversions of the various nitrogen oxides that are based on metal–ligand coordination complexes, looking in particular at more recent examples that take inspiration from the natural systems.